Losses Associated With Childhood Sexual Abuse in Women Survivors: A Scoping Review. (December 2022) - Kays Ebrahim, Baaqira; Fouche, Ansie; Walker-Williams, Hayley
Childhood sexual abuse is a complex trauma with unique trauma-causing factors that could have devastating long-term, negative effects on survivors. To date, little attention has been given to loss and specifically stigmatized or hidden loss as a unique trauma-causing factor. Method: This article reports the findings of a scoping review designed to identify research exploring the losses associated with childhood sexual abuse in women survivors. A systematic search of databases for articles published between 1983 and 2019 were conducted using keywords related to loss and women survivors of childhood sexual abuse. Findings: Twenty studies were selected for review using predefined inclusion criteria: studies that include adult women survivors of childhood sexual abuse, studies that include child/childhood sexual abuse, studies that include stigmatized loss, studies that indicate stigmatized loss in adult women survivors of childhood sexual abuse. Sources were subject to quality appraisal and data were extracted in line with the review question. Discussion and Contribution: Findings acknowledged and extended on Bloom's model of stigmatized loss and suggested that female survivors of childhood sexual abuse may experience an overall loss of self-efficacy, presenting as a loss of personal agency, interpersonal agency, and sexual agency. The results of this research suggest that loss be considered in support interventions with women self-reporting childhood sexual abuse. It is recommended that further research be conducted to confirm these findings so that they may advocate for inclusion in childhood sexual abuse treatment interventions.